Biomarkers in Colorectal Cancer: The Role of Translational Proteomics Research - Alves Martins, Bruno Augusto; de Bulhões, Gabriel Fonseca; Cavalcanti, Igor Norat; Martins, Mickaella Michelson; de Oliveira, Paulo Gonçalves; Martins, Aline Maria Araújo (Frontiers in Oncology, 2019)
Colorectal cancer is one of the most common cancers in the world, and it is one of the leading causes of cancer-related death. Despite recent progress in screening programmes and in the management of patients with colorectal cancer, there are still many gaps to fill to establish a personalized approach, ranging from the prevention and early diagnosis to the determination of prognosis factors and treatment of metastatic disease. The genetic profile approach has been increasingly used in the decision-making process, especially in the choice of targeted therapies and in the prediction of drug response, but there are still few validated biomarkers of colorectal cancer for clinical practice. The discovery of noninvasive, sensitive and specific biomarkers is an urgent need, and translational proteomics plays a key role in this process, as it enables better comprehension of colorectal carcinogenesis, identification of potential markers and subsequent validation. This review provides an overview of recent advances in the search for colorectal cancer biomarkers through proteomics studies, according to biomarker function and clinical application.